ANALISIS PELAKSANAAN PENGELOLAAN ROYALTI HAK CIPTA LAGU DAN MUSIK OLEH LEMBAGA MANAJEMEN KOLEKTIF NASIONAL BERDASARKAN PERATURAN PEMERINTAH NO. 56 TAHUN 2021 - Jevano Tri Alexander; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
Songs or music are copyrighted works that are protected by copyright. Every Creator or Related Rights owner will get his economic rights in the form of royalties, if there are users or public service places that use songs or music for commercial purposes. Recently, the president signed and ratified the government's law and regulation Number 56 of 2021 regarding the management of royalties on song and/or music copyrights. This PP was issued to optimize and provide legal protection and certainty to the creator or the author's rights regarding song copyright royalties. So that all business people where public services are listed in the PP, such as cafes, restaurants, music concerts, cinemas, karaoke, and others, when using songs or playing songs created by others for commercial purposes are required to pay royalties through LMKN. The LMKN is an institution that has the authority to collect royalties for song and/or music copyrighted works from commercial users. However, how does LMKN conduct supervision in supervising commercial users and so that this Government Regulation is enforced? The PP also does not explain how LMKN supervises and monitors these public service places. As well as places of public service are also very widely spread throughout Indonesia. Therefore, LMKN really needs to pay attention to the mechanism for managing the collection of song and/or music copyright royalties so that creators and musicians in Indonesia are guaranteed legal protection and LMKN actually carries out their obligations as stated in PP 56 of 2021